Disease burden of spinal muscular atrophy in Germany. Issue 1 (December 2016) - Klug, Constanze; Schreiber-Katz, Olivia; Thiele, Simone; Schorling, Elisabeth; Zowe, Janet; Reilich, Peter; Walter, Maggie; Nagels, Klaus
Abstract Background This study aimed at analyzing the economic burden and disease-specific health-related quality of life (HRQOL) of patients with spinal muscular atrophy (SMA) in Germany. SMA is a so far non-curable neuromuscular disease of the anterior nerve cells that causes high rates of morbidity and mortality. Methods In a cross-sectional study we analyzed the cost of illness (COI) and factors that influence the direct, indirect and informal care costs of affected patients and their families by using standardized, self-developed questionnaires. We used the PedsQL™© Measurement Model to analyze the disease-specific HRQOL of patients. Results One hundred eighty nine patients with SMA types I to III aged <1 to 73 years were enrolled. The average annual COI was estimated at €70, 566 per patient in 2013. The highest cost resulted in SMA I with significant lower costs for the milder phenotypes. Inversely, the self-estimated HRQOL increased from SMA I to SMA III. Major cost drivers were informal care cost and indirect cost incurred by patients and their caregivers. Conclusions Although SMA requires high standards of care, there has been a distinct lack of health services research on SMA. Accordingly, our results significantly contribute to a more comprehensive insight into the current burden of SMA and quality of life status as related to SMA health services in Germany. In the light of innovative therapeutic interventions, our results suggest a notable potential for a reduction in overall COI and improvement of HRQOL if the therapeutic intervention leads to a less severe course of the disease.